Analysis of The Organizational Readiness of The Secretariat General of The House of Representatives of The Republic of Indonesia to Face The Era of Open Government and Open Parliament In The Scenario Planning Approach Towards 2035 - Aprilia Dessy Kurniati; Ima Mayasari (Green Publisher Indonesia, 2025)
This study examines the organizational readiness of the Secretariat General of the House of Representatives of Indonesia in adapting to the challenges posed by open government and open parliament initiatives. The main issue addressed is the lack of synchronization between government openness policies and parliamentary openness efforts in Indonesia. The objective of this research is to explore possible future scenarios for the Secretariat General through scenario planning, a method that provides a strategic framework to navigate uncertain and complex environments. The research utilizes the TAIDA framework (Tracking, Analyzing, Imaging, Deciding, and Acting) to identify key drivers of change and map out potential futures. The results suggest four possible scenarios ranging from a fully aligned, innovative, and efficient Secretariat General to one that lags behind in adapting to these changes. The implications of this study are significant for policymakers, providing strategic insights into how the Secretariat General can improve organizational readiness, enhance public participation, and strengthen governance transparency to align with global trends of openness. These findings offer a roadmap for strengthening Indonesia’s parliamentary system and its commitment to open governance